Study on the Relocation of Blambangan Traditional Market in Banyuwangi Regency: A Policy Formulation Perspective - Muhammad, Juang Abdi; Rahman, Auliya Gaffar (Universitas 17 Agustus 1945 Surabaya, 2025)
Traditional markets play an important role in the regional economy as a center of trade and social and cultural interaction. The Banyuwangi Regency Government relocated and revitalized Blambangan Market to improve the quality of infrastructure and the competitiveness of traditional markets. However, this policy poses challenges for traders, especially in terms of decreasing the number of visitors to the relocation location, which has an impact on decreasing their income. This study analyzes the Blambangan Market relocation policy through William N. Dunn's policy formulation approach, referring to the 2021-2026 Banyuwangi Regency RPJMD. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and literature studies. The results of the study indicate that the relocation policy has not optimally considered the economic and social aspects of traders. The main factors of the problem are the lack of two-way communication between the government and traders, low accessibility at the relocation location, and the lack of adaptation strategies for traders. The problem structuring and forecasting approaches in the analysis of policy formulation indicate that without proper intervention, traders tend to return to their old locations, which has the potential to cause disorder in urban spatial planning. As a solution, this study recommends strategies to improve two-way communication, intensive promotion to attract visitors to the relocation site, providing incentives to traders, and improving accessibility and infrastructure in the new location. With a more participatory and adaptive policy approach, market relocation can run more effectively and provide long-term benefits for the regional economy.